THE PHILOSOPHICAL AND SPIRITUAL MEANING OF THE IDDAH PERIOD IN ISLAM: Its Influence on the Formation of the Character of Muslim Women - Lailatul Qadariyah; Nor Hasan (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
The iddah period in Islam is the period lived by women after divorce or the death of their husband, which has a deep meaning both philosophically and spiritually. This research aims to examine the philosophical and spiritual meaning of the iddah period and its influence on the formation of the character of Muslim women. The study also identified that iddah plays a role in shaping the character of Muslim women by teaching patience, wisdom, and maturity in the face of life's trials. Psychologically, the iddah period helps women cope with the loss and trauma caused by divorce or death of a partner. In addition, the iddah period also provides time for women to adjust to society after changes in their social status. In the social context, iddah helps women to return to improving social relationships and live a more independent life. The results of this study show that the iddah period is not only a legal obligation, but also an important process in women's spiritual, emotional, and social self-development, as well as contributing to the formation of a stronger and more mature character.